Contextualizing Martial Arts Pedagogy in Early Childhood Education: Taekwondo and the Development of Gross Motor Competence in Indonesia - Anita Damayanti; Ummatun Najiha; Eka Mawar Izzatuttadzkiroh; Festo Beda Nguru; Frank Angelo Abayog Pacala; Francis Kyambo William (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Background of the study: Gross motor competence in early childhood predicts later physical literacy, academic readiness, and psychosocial adjustment. Although structured physical activity is increasingly integrated into early childhood education, research on martial arts–based extracurricular programs for preschoolers remains limited, particularly within formal institutional settings in developing contexts. Aims and scope of paper: This study examines how a developmentally adapted Taekwondo extracurricular program supports gross motor development among children aged 5–6 years at TK Kemala Bhayangkari 79, Indonesia. It analyzes both the pedagogical structure of the program and its developmental implications within movement-based early childhood education. Methods: A qualitative phenomenological case study design was employed to explore participants’ lived experiences and institutional practices. Data were collected through non-participant observations of training sessions, semi-structured interviews with the head coach, assistant coach, and school principal, and document analysis. Participants included enrolled children and adult stakeholders involved in implementation. Data were analyzed using the interactive model of Miles and Huberman, including data condensation, display, and conclusion drawing to ensure analytical rigor. Results: The Taekwondo program, initiated in September 2025, was developmentally structured with warm-ups, core technique practice, and cool-down phases emphasizing discipline, emotional regulation, and playful engagement. Supported by tiered supervision from coaches and teachers, the program enhanced children’s balance, coordination, strength, flexibility, body control, concentration, and behavioral self-regulation. Effective implementation relied on coaches’ pedagogical sensitivity and age-appropriate communication. Contribution: This study reconceptualizes martial arts as a developmentally responsive pedagogical intervention rather than merely a competitive sport. Situated in Indonesia as part of the Global South, it provides context-sensitive evidence that challenges Western-centric models of physical literacy and expands theoretical discussions on culturally responsive physical education in early childhood. The findings also call for mixed-method and quasi-experimental research to strengthen causal inference and scalability across diverse educational contexts.